Nilai Pendidikan Dan Psikologi Tokoh Dalam Lontar Satua I Naga Gombang - Ni Wayan Tika Triska Dewi; I Wayan Sugita; I Wayan Artayasa (Cetta: Jurnal Ilmu Pendidikan, 2019)
Lontar is one of Bali Purwa literature which is still sustainable until now. Lontar can be used as a means of learning because full of religious teachings are used as guidance in the daily life. One of the lontars is Lontar Satua I Naga Gombang. This study examines three problem formulas: (1) How is the intrinsic structure contained in the lontar of Satua I Naga Gombang ?, (2) What is the value of education contained in Lontar Satua I Naga Gombang ?, (3) How is the psychology of figures contained in Lontar Satua I Naga Gombang ?. Theories used to explain the problem formulation are: (1) Structural Theory, (2) Value theory, (3) Psychological theory. The research method used is qualitative method. The techniques used in data collection are library techniques, documentation and transliteration. Furthermore, the data analysis using descriptive qualitative methods. Analysis of data used in research there are three namely: data reduction, data presentation and data deduction. The results of the research explain the intrinsic structure contained in lontar that is incident, plot, character and characterization, setting, theme and message. The value of education contained in the palm of Lontar Satua I Naga Gombang namely ethical values, divinity, loyalty value and karma phala value. Furthermore, the psychology of figures contained in Lontar Satua I Naga Gombang is the psychology of figures from I Naga Gombang, the psychology of figures Galuh Daha, the psychology of figures Semara Jaya (Naga Rarik), the psychology of figures Kencana wati (Raden Galuh), the psychology of figures Sang Hyang Guru and the psychology of figures I Mara Pati (Raden Mantri).